On some systems of convolution-type first-order integrodifferential equations on the semiaxis - Khachatryan, A. Kh.; Khachatryan, Kh. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study a class of vector convolution-type integrodifferential equations on the semiaxis used for the description of various applied problems of mathematical physics. By using a special three-factor decomposition of the original mathematical integrodifferential operator, we prove the solvability of these equations in certain functional spaces.